At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To graph the function [tex]\(y = \cos \left( \frac{3\pi}{4} \right) \sin (x) + \cos (x) \sin \left( \frac{3\pi}{4} \right)\)[/tex] over the interval [tex]\( [-2\pi, 2\pi] \)[/tex], we need to first rewrite it using trigonometric identities. Here's the detailed, step-by-step solution:
1. Use the Angle Sum Identity for Sine:
The given function is of the form [tex]\( \cos(A) \sin(x) + \cos(x) \sin(A) \)[/tex]. Using the sum identity for sine, we know:
[tex]\[ \sin(A + x) = \sin(x) \cos(A) + \cos(x) \sin(A) \][/tex]
2. Match the Given Expression:
By comparing the given function to the sine sum identity, it is clear that:
[tex]\[ y = \cos \left( \frac{3\pi}{4} \right) \sin (x) + \cos (x) \sin \left( \frac{3\pi}{4} \right) \][/tex]
corresponds to:
[tex]\[ y = \sin \left( x + \frac{3\pi}{4} \right) \][/tex]
3. Simplify Using Trigonometric Values:
Let's verify the trigonometric values used in the identity:
- [tex]\( \cos \left( \frac{3\pi}{4} \right) = -\frac{\sqrt{2}}{2} \)[/tex]
- [tex]\( \sin \left( \frac{3\pi}{4} \right) = \frac{\sqrt{2}}{2} \)[/tex]
Therefore, we indeed have:
[tex]\[ y = \sin \left( x + \frac{3\pi}{4} \right) \][/tex]
4. Graphing the Function:
Now that we have the function in a simpler form, [tex]\( y = \sin \left( x + \frac{3\pi}{4} \right) \)[/tex], we can proceed to graph it. Here's how:
- Original Sine Function: Recall that the basic [tex]\( y = \sin(x) \)[/tex] function oscillates between [tex]\(-1\)[/tex] and [tex]\(1\)[/tex] with a period of [tex]\(2\pi\)[/tex], crossing the x-axis at [tex]\(0, \pi, 2\pi\)[/tex] (and their negative counterparts).
- Phase Shift: The function [tex]\( y = \sin \left( x + \frac{3\pi}{4} \right) \)[/tex] is a horizontal shift of [tex]\( y = \sin(x) \)[/tex] to the left by [tex]\( \frac{3\pi}{4} \)[/tex].
- Interval [tex]\([-2\pi, 2\pi]\)[/tex]:
- For [tex]\( x = -2\pi \)[/tex]:
[tex]\[ y = \sin \left( -2\pi + \frac{3\pi}{4} \right) = \sin \left( -\frac{5\pi}{4} \right) \][/tex]
- For [tex]\( x = 0 \)[/tex]:
[tex]\[ y = \sin \left( 0 + \frac{3\pi}{4} \right) = \sin \left( \frac{3\pi}{4} \right) = \frac{\sqrt{2}}{2} \][/tex]
- For [tex]\( x = 2\pi \)[/tex]:
[tex]\[ y = \sin \left( 2\pi + \frac{3\pi}{4} \right) = \sin \left( \frac{11\pi}{4} \right) \][/tex]
5. Sketching the Graph:
- Draw the [tex]\( y = \sin(x) \)[/tex] curve.
- Shift this curve to the left by [tex]\( \frac{3\pi}{4} \)[/tex].
The resultant graph should show a sine wave starting at [tex]\( -2\pi \)[/tex] and ending at [tex]\( 2\pi \)[/tex], shifted to reflect the phase shift of [tex]\( \frac{3\pi}{4} \)[/tex]. The values and crossings will all be adjusted according to this shift.
This completes the step-by-step explanation of how to rewrite and graph the given trigonometric function.
1. Use the Angle Sum Identity for Sine:
The given function is of the form [tex]\( \cos(A) \sin(x) + \cos(x) \sin(A) \)[/tex]. Using the sum identity for sine, we know:
[tex]\[ \sin(A + x) = \sin(x) \cos(A) + \cos(x) \sin(A) \][/tex]
2. Match the Given Expression:
By comparing the given function to the sine sum identity, it is clear that:
[tex]\[ y = \cos \left( \frac{3\pi}{4} \right) \sin (x) + \cos (x) \sin \left( \frac{3\pi}{4} \right) \][/tex]
corresponds to:
[tex]\[ y = \sin \left( x + \frac{3\pi}{4} \right) \][/tex]
3. Simplify Using Trigonometric Values:
Let's verify the trigonometric values used in the identity:
- [tex]\( \cos \left( \frac{3\pi}{4} \right) = -\frac{\sqrt{2}}{2} \)[/tex]
- [tex]\( \sin \left( \frac{3\pi}{4} \right) = \frac{\sqrt{2}}{2} \)[/tex]
Therefore, we indeed have:
[tex]\[ y = \sin \left( x + \frac{3\pi}{4} \right) \][/tex]
4. Graphing the Function:
Now that we have the function in a simpler form, [tex]\( y = \sin \left( x + \frac{3\pi}{4} \right) \)[/tex], we can proceed to graph it. Here's how:
- Original Sine Function: Recall that the basic [tex]\( y = \sin(x) \)[/tex] function oscillates between [tex]\(-1\)[/tex] and [tex]\(1\)[/tex] with a period of [tex]\(2\pi\)[/tex], crossing the x-axis at [tex]\(0, \pi, 2\pi\)[/tex] (and their negative counterparts).
- Phase Shift: The function [tex]\( y = \sin \left( x + \frac{3\pi}{4} \right) \)[/tex] is a horizontal shift of [tex]\( y = \sin(x) \)[/tex] to the left by [tex]\( \frac{3\pi}{4} \)[/tex].
- Interval [tex]\([-2\pi, 2\pi]\)[/tex]:
- For [tex]\( x = -2\pi \)[/tex]:
[tex]\[ y = \sin \left( -2\pi + \frac{3\pi}{4} \right) = \sin \left( -\frac{5\pi}{4} \right) \][/tex]
- For [tex]\( x = 0 \)[/tex]:
[tex]\[ y = \sin \left( 0 + \frac{3\pi}{4} \right) = \sin \left( \frac{3\pi}{4} \right) = \frac{\sqrt{2}}{2} \][/tex]
- For [tex]\( x = 2\pi \)[/tex]:
[tex]\[ y = \sin \left( 2\pi + \frac{3\pi}{4} \right) = \sin \left( \frac{11\pi}{4} \right) \][/tex]
5. Sketching the Graph:
- Draw the [tex]\( y = \sin(x) \)[/tex] curve.
- Shift this curve to the left by [tex]\( \frac{3\pi}{4} \)[/tex].
The resultant graph should show a sine wave starting at [tex]\( -2\pi \)[/tex] and ending at [tex]\( 2\pi \)[/tex], shifted to reflect the phase shift of [tex]\( \frac{3\pi}{4} \)[/tex]. The values and crossings will all be adjusted according to this shift.
This completes the step-by-step explanation of how to rewrite and graph the given trigonometric function.
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.